2000
DOI: 10.1021/ic0005137
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Sterically Encumbered Terphenyl-Substituted Species 2,6-Trip2H3C6S̈n−Sn(Me)2C6H3-2,6-Trip2, an Unsymmetric, Group 14 Element, Methylmethylene, Valence Isomer of an Alkene, Its Related Lithium Derivative 2,6-Trip2H3C6(Me)2Sn−Sn(Li)(Me)C6H3-2,6-Trip2, and the Monomer Sn(t-Bu)C6H3-2,6-Trip2 (Tri

Abstract: The reaction of the recently reported sterically encumbered terphenyl tin(II) halide species Sn(Cl)C6H3-2,6-Trip2 (Trip = C6H2-2,4,6-i-Pr3), 1, with 1 equiv of MeLi or MeMgBr afforded 2,6-Trip2H3C6Sn-Sn(Me)2C6H3-2,6-Trip2, 2, which is the first stable group 14 element methylmethylene (i.e., CH3CH) analogue of ethylene (H2CCH2). Reaction of 1 with 1.5 equiv of MeLi yielded the stannylstannate species 2,6-Trip2H3C6(Me)2Sn-Sn(Li)(Me)-C6H3-2,6-Trip2, 3, whereas reaction of 1 with 1 equiv of t-BuLi gave the heterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 26 publications
4
28
0
Order By: Relevance
“…The data for 1 show that the C ipso –Sn–C angle is 98.15(6)°, with a very similar C ipso –Sn–C angle of 98.63(7)° being observed for 2 . The C ipso –Sn bond lengths in 1 and 2 span the narrow range of 2.1994(17)–2.2054(16) Å and are similar to those previously reported by this group and by others (2.168(8)–2.204(8) Å) , as well as being close to the sum (2.17 Å) of the single bond radii of carbon (0.77 Å) and tin (1.40 Å) . The C ethenyl –Sn bond lengths are 2.2020(17) Å in 1 and 2.2061(18) Å in 2 .…”
Section: Resultssupporting
confidence: 85%
“…The data for 1 show that the C ipso –Sn–C angle is 98.15(6)°, with a very similar C ipso –Sn–C angle of 98.63(7)° being observed for 2 . The C ipso –Sn bond lengths in 1 and 2 span the narrow range of 2.1994(17)–2.2054(16) Å and are similar to those previously reported by this group and by others (2.168(8)–2.204(8) Å) , as well as being close to the sum (2.17 Å) of the single bond radii of carbon (0.77 Å) and tin (1.40 Å) . The C ethenyl –Sn bond lengths are 2.2020(17) Å in 1 and 2.2061(18) Å in 2 .…”
Section: Resultssupporting
confidence: 85%
“…All 1 H, 13 C­{ 1 H}, and 119 Sn­{ 1 H} NMR spectroscopic data are listed in greater detail in the Supporting Information. The 119 Sn­{ 1 H} NMR spectrum of 2a was recorded at 330 K and displayed a broad resonance at 1908 ppm which lies within the previously reported range for monomeric stannylene species (442–2235 ppm) , and is similar to that in the monomer Ar i Pr 6 Sn t Bu at 1904 ppm, indicating that 2a dissociates to the monomer Ar i Pr 6 Sn­(C 2 H 5 ) in solution at room temperature. The 1 H NMR spectrum of 2a was recorded at 330 K in a d 8 -toluene solution.…”
Section: Resultssupporting
confidence: 80%
“…They also undergo several facile reactions that include C–H activation and the hydroelementation of small molecules. , Roesky and co-workers reported that the monomeric Sn­(II) hydride, [HC­(CMeNAr) 2 ]­SnH (Ar = 2,6- i Pr 2 C 6 H 3 ), could hydrostannylate ketones, CO 2 , and terminal alkynes to give Sn­(II) alkoxides, stannylene formates, and alkenyl stannylenes. Jones and co-workers used the bulky amido ligand, −N­(Ar † )­(SiPr i 3 ) (Ar † = C 6 H 2 -2,6-{C­(H)­Ph 2 } 2 -4- i Pr), to stabilize a singly bonded digermyne which reacted with H 2 to form monomeric Ar † (SiPr i 3 )­NGeH that catalyzed the hydroboration of carbonyl groups to afford alcohols . In addition, in situ generated Sn­(II) hydrides were shown to catalyze the dehydrocoupling of amines and boranes. , The high reactivity of the group 14 metal hydrides ArEH (E  Ge, Sn) is due to their partially open shell structures which have an occupied s and an empty p-orbital which can interact with the frontier orbitals of unsaturated hydrocarbons and related molecules. , …”
Section: Introductionmentioning
confidence: 99%
“…Stannylenes are mostly coloured in hydrocarbon solution due to their symmetry forbidden n-p transition in the visible region. [34][35][36][37][38][39][40][41][42] As shown in Fig. 2, both 2a and 2b feature two broad absorption bands.…”
mentioning
confidence: 92%